(untitled) (International Journal of Engineering and Computer Science, 2013)
In video streaming over multicast network,user bandwidth requirement is often heterogeneous possibly with orders of magnitude difference (say, from hundreds of kb/s for mobile devices to tens of mb/s for high-definition TV).Multiple descry ption coding (MDC) can be used to address this bandwidth heterogeneity issue. In MDC, the video source is encoded into multiple independent descriptions. A receiver, depending on its available bandwidth, joins different descriptions to meet their bandwidth requirements.An important but challenging problem for MDC video multicast is how to assign bandwidth to each description in order to maximize overall user satisfaction. In this paper,we investigate this issue by formulating it as an optimization problem, with the objective to maximize user bandwidth experience by taking into account then coding inefficiency due to MDC. We prove that the optimization problem is NP-hard. However, if the description number is larger than or equal to a certain threshold(e.g., if the minimum and maximum bandwidth requirements are100 kb/s and 10 mb/s, respectively, such threshold is seven descriptions), there is an exact and simple solution to achieve maximum user satisfaction, i.e., meeting all the bandwidth requirements. For the case when the description number is smaller, we present an efficient heuristic called simulated annealing for MDC bandwidth assignment(SAMBA) to assign bandwidth to each description given the distribution of user bandwidth requiremen.We evaluate our algorithm using simulations. SAMBA achieves virtually the same optimal performance based on exhaustive search .By comparing with other assignment algorithms, SAMBA significantly improves user satisfaction. We also show that, if the coding efficiency decreases with the number of descriptions, there is an optimal description number to achieve maximal user satisfaction.